2013
DOI: 10.1111/jvim.12137
|View full text |Cite
|
Sign up to set email alerts
|

Serum Serotonin Concentration Is Associated with Severity of Myxomatous Mitral Valve Disease in Dogs

Abstract: Background: The neurotransmitter serotonin (5-hydroxytryptamine, 5-HT) has recently been suggested to play a role in the development of naturally acquired myxomatous mitral valve disease (MMVD) in dogs.Aim: To investigate the association between serum 5-HT concentration and MMVD severity in dogs, and to assess potential associations between serum 5-HT concentrations and dog characteristics, echocardiographic variables, heart rate, systolic blood pressure, presence of macrothrombocytosis, and plateletcrit.Anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
68
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(87 citation statements)
references
References 58 publications
16
68
3
Order By: Relevance
“…A significant low 5-HT concentration was found between control and moderate to severe groups, although there were no differences between the control and mild group, and between the mild and the moderate to severe group. These findings are similar to the previous study that 5-HT concentration was decreasing with increasing MMVD severity and high 5-HT levels in early stages of MMVD are associated with the development of MMVD [8].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A significant low 5-HT concentration was found between control and moderate to severe groups, although there were no differences between the control and mild group, and between the mild and the moderate to severe group. These findings are similar to the previous study that 5-HT concentration was decreasing with increasing MMVD severity and high 5-HT levels in early stages of MMVD are associated with the development of MMVD [8].…”
Section: Discussionsupporting
confidence: 82%
“…The result is similar to that of Ljungvall [8]. Also, dogs with moderate to severe MMVD had significantly lower serum 5-HT concentrations than the control group in the obese groups.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Serum CXCL8, CCL2, and VEGF measurements were performed using commercial canine ELISA kits (R&D Systems) in duplicate, according to the manufacturer's instructions. Serum 5-HT measurement was performed using a commercial human ELISA kit (IBL international) previously validated in dogs (Ljungvall et al, 2013).…”
Section: Samples Processingmentioning
confidence: 99%
“…In humans, altered regulation of the serotonin pathway is thought to be associated with the development of pulmonary fibrosis since an increased expression of 5-HT receptors was found in IPF lungs (Fabre and Crestani, 2010;Konigshoff et al, 2010) and anti-serotonin therapy was shown to attenuate induced pulmonary fibrosis in mice (Konigshoff et al, 2010;Skurikhin et al, 2012). In dogs, 5-HT has essentially been studied in the pathogenesis of the DMVD, another fibrotic disease (Oyama and Levy, 2010;Ljungvall et al, 2013;Cremer et al, 2014;Mangklabruks and Surachetpong, 2014). Increased 5-HT blood concentrations were found in healthy KCS in comparison with healthy dogs from other breeds predisposed or not to DMVD (Arndt et al, 2009).…”
Section: Serum 5-ht Concentrationsmentioning
confidence: 99%